Ensuring optimal metabolism during coronary artery bypass grafting with cardiopulmonary bypass - V. I. Cherniy; L. O. Sobanska (Patologìâ)
Aim: to reduce perioperative complications in cardiac surgeries with cardiopulmonary bypass (CPB) by developing a comprehensive, personalized approach to ensure optimal tissue metabolism.